Utilization of Flora in the School Environment as a Drawing Medium for Reading Children's Creativity - Okta, Setyo Luthfi; Surya, Dhika; Zenklinov, Amanatullah Pandu (Research Collaboration Community (RCC), 2025)
This study examines the use of flora in the school environment as an alternative media to develop children's creativity through drawing activities. Using qualitative methodology with a descriptive approach, the study involved 19 elementary school students in an experiment based on the exploration of natural elements. The research instruments included participatory observation, documentation of work, and structured interviews. The results showed a significant increase in the dimensions of creativity, with indicators: a 40% increase in the quality of geometric patterns, 40% in color exploration, and 40% in abstract composition. Student involvement reached 90% with a high level of enthusiasm in the creative process. The findings indicate that flora media can stimulate imaginative capacity, encourage artistic experimentation, and broaden students' creative perspectives in the context of continuing art education.